Characterizing watercraft‐related mortality of sea turtles in Florida. Issue 5 (20th May 2019) - Foley, Allen M.; Stacy, Brian A.; Hardy, Robert F.; Shea, Colin P.; Minch, Karrie E.; Schroeder, Barbara A.
ABSTRACT: Mortality from being struck by a motorized watercraft is considerable for many aquatic vertebrates around the world, including sea turtles. We studied stranded (i.e., dead, sick, or injured) sea turtles found in Florida, USA, during 1986–2014 and identified those with sharp force or blunt force injuries indicative of a vessel strike. About a third of stranded loggerheads ( Caretta caretta ), green turtles ( Chelonia mydas ), and leatherbacks ( Dermochelys coriacea ) had a vessel‐strike injury (VSI). The frequency of this injury was lower but still substantial for stranded Kemp's ridleys ( Lepidochelys kempii ; 26.1%) and hawksbills ( Eretmochelys imbricata ; 14.8%). Over the study period, the annual number of stranded loggerheads, green turtles, and Kemp's ridleys with a VSI increased as did the annual number of vessels registered in Florida. Eighty‐one percent of the stranded turtles with a VSI were found in the southern half of Florida and 66% of those were found along the southeast coast. By coastal county, the proportion of stranded sea turtles with a VSI was positively related to the mean annual number of registered vessels. The percentage occurrence of a VSI was highest for adult loggerheads, green turtles, and leatherbacks, and reproductively active individuals appeared to be particularly vulnerable to these injuries. We conducted necropsies on 194 stranded sea turtles with a VSI and concluded that this injury was the cause of death or the probable cause of death in ≥92.8% of these cases. During 2000–2014, we estimate that the mean annual numbers of stranded sea turtles that died from a VSI were 142–229 loggerheads, 101–162 green turtles, 16–32 Kemp's ridleys, 4–6 leatherbacks, and 2–4 hawksbills. Considering that only about 10–20% of sea turtles that died likely washed ashore, the overall annual mortality may have been 5–10 times greater than that represented by strandings. Most of the significant clusters of stranded sea turtles with a VSI occurred at inlets or passes and the probability that a stranded sea turtle had a VSI decreased with increasing distance from inlets or passes, navigable waterways, and marinas. We suggest focusing initial management efforts on reducing watercraft‐related mortality for all sea turtle species around 8 inlets in southeast Florida, reproductively active loggerheads and green turtles along the coast of southeast Florida, and Kemp's ridleys and adult male loggerheads at passes along the coast of southwest Florida. Published 2019. This article is a U.S. Government work and is in the public domain in the USA. The Journal of Wildlife Management published by Wiley Periodicals, Inc. on behalf of The Wildlife Society Abstract : Watercraft‐related mortality of sea turtles in Florida is substantial and reproductively active adults appear to be particularly vulnerable. Initial efforts to reduce this mortality should focus on southeast Florida, especially around 8 inlets where this mortality is particularly high.